Hierarchical porous ZnMn2O4 microspheres assembled by nanosheets for high performance anodes of lithium ion batteries. Issue 10 (7th September 2017) - Zeng, Junsong; Ren, Yanbiao; Wang, Shengbin; Hao, Yu; Wu, Hao; Zhang, Shichao; Xing, Yalan
Abstract : Hierarchical porous ZnMn2 O4 microspheres assembled by nanosheets are fabricated and they exhibit outstanding electrochemical performance for lithium-ion battery anodes. Abstract : Hierarchical porous ZnMn2 O4 microspheres assembled by nanosheets with an average thickness of several nanometers are successfully synthesized by a facile hydrothermal method and subsequent calcination at 500 °C in air. When used as an anode electrode of lithium ion batteries (LIBs), the ZnMn2 O4 microspheres exhibit a high discharge capacity of 1132 mA h g −1 after 500 cycles at a current density of 500 mA g −1 and excellent rate capability. It is believed that the outstanding electrochemical performance benefits from the hierarchical porous structure that can not only increase the contact area between the electrode and the electrolyte to facilitate the transfer of Li + ions, but also provide sufficient space for volume expansion of the electrode during the cycling process.